2016
DOI: 10.3390/su8080755
|View full text |Cite
|
Sign up to set email alerts
|

Sustainability Commitment, New Competitors’ Presence, and Hotel Performance: The Hotel Industry in Barcelona

Abstract: Abstract:The hospitality industry is facing major challenges, among them the new competition from novel forms of supply in the sharing economy. Airbnb, Homeaway, and Niumba, among other websites offering accommodations, are having an important impact in the sector, changing existing conditions and the market for the traditional hospitality industry. In this context, a strategy based in differentiation can help to prevent drops in revenues and profitability. The main objective of this paper is analyse if commit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
2
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(35 citation statements)
references
References 28 publications
1
26
2
6
Order By: Relevance
“…The results of this study reject the results of research conducted by Aznar et al (2016). Environmental commitment in the company does not show a significant relationship with the company's performance due to a lack of proactive consumer attitudes so that the differentiation of companies with environmental commitments will not result in better financial performance.…”
Section: Effect Of Environmental Commitment On Financial Performancecontrasting
confidence: 94%
See 2 more Smart Citations
“…The results of this study reject the results of research conducted by Aznar et al (2016). Environmental commitment in the company does not show a significant relationship with the company's performance due to a lack of proactive consumer attitudes so that the differentiation of companies with environmental commitments will not result in better financial performance.…”
Section: Effect Of Environmental Commitment On Financial Performancecontrasting
confidence: 94%
“…The results of the Sobel Test and mediation requirements by Baron and Kenny (1986) show that green product innovation is not able to be a link between the influence of environmental commitment on financial performance so that hypothesis 7 (H7) is rejected. This is consistent with research conducted by Grekova et al (2013) and Aznar et al (2016) where green product innovation is not able to be a link between the influence of environmental commitment on financial performance, explaining that additional skills and knowledge are needed to innovate because of the high complexity of green product innovation rather than other innovations.…”
Section: Effect Of Environmental Commitment On Financial Performance supporting
confidence: 89%
See 1 more Smart Citation
“…Only one study found negative impacts [32], however this was presumably due to the rather small geographical scope, as a similar study conducted two years later by the same authors with a larger geographic scope, found a positive impact [29]. Though there has been some uncertainty regarding impact [33,34], the source of the eco-label, that is whether from government or NGOs as compared to corporate or corporate association established eco-labels, has been found to be an indication of credibility and trustworthiness in the green market [33,35].…”
Section: Effects That Sustainability Practices Have On Financial and mentioning
confidence: 99%
“…Quadro 1 -Artigos selecionados que compõem a revisão sistemática da literatura. (Aznar et al, 2016, Birinci et al, 2018Hajibaba & Dolnicar, 2017;Kljucnikov et al, 2018;Varma et al, 2016;Volgger et al, 2018) Prayag e Ozanne (2018), por outra perspectiva, trabalham a ideia da transição tecnológica por meio da inovação disruptiva. Para os autores, o regime sociotécnico onde ocorre a inovação sempre será resiliente e resistente à mudança, e os nichos que surgem são os responsáveis por confrontar esta resiliência por seu espaço no mercado: "Nós argumentamos que mudanças disruptivas a nível geral criam oportunidades para atores de nichos específicos inovarem nos modelos de meios de hospedagem, tais como a hospedagem compartilhada pessoa-a-pessoa."…”
Section: Percurso Metodológicounclassified